Candombe mineiro: É dingoma/ Saravano tambu/ Peço licença/ Pro meu canto firmá - Ridalvo Felix de Araújo (2017)
This thesis is dedicated to analyze the generic use of the word batuque, used to designate some African and Afro-Brazilian traditions, as well as those of African matrices found in Portugal. We sought to discuss how the Batuque designation arose, considering the contact of the Portuguese with the Africans and their descendants in America and Europe. In order to do so, we describe some traditions - recorded according to the meaning of batuque in each context and the affinities presented in the technique of producing the instruments and in the performances of the dancing chants - that configure, to a large extent, the Bantu linguistic and cultural heritage. To exemplify, we approach Batuku, from Cape Verde and Portugal; Batuque, from Rio Grande do Sul; Batuque, from Amapá; Batuque de umbigada, from São Paulo; and finally, Batuque from Minas Gerais, with representations occurring in São Romão, in the Gorutuban region, and in the community of the Arturos in Contagem. In the diverse universe of expressions of Afro-Brazilian dancing chants, we focused specifically on the Candombe from Minas Gerais and its great variety of ngomas. We will present some groups of this tradition, especially regarding the aesthetics of the set of drums, thus bringing some expressions of Mozambique. In this perspective, we reflect on the art of performing the dancing chants, and also the foundational narratives of the Candombe tradition, analyzing the poetic aspects and variations between the songs of dancing chants in the last days during the rituals practiced at Festejos do Rosário, and the repertoire registered in the manuscripts of Capitão David. The interviews and the relationship with Capitão David, from Candombe da Lapinha, in Lagoa Santa, Minas Gerais, led to the discovery - and to the book edition - of the manuscripts in which he recorded chants and narrations from the Candombe tradition, and its importance is the essential motivation that led to the construction of this work. These manuscripts are analyzed as a way found by the Capitão to record a memory of the tradition, especially of the knowledge transmitted by ancestors that integrate a culture of the voice within the community. Finally, to illustrate, we present a description of two rituals, from the Candombe of Captain David, linked to the Feast of the Rosary: an opening ritual and a closing ritual of the activities of this group, whose focus is on the performance practices of transmission of the dancing chants and ways to play the tambo from the tradition for beginners children.